PENGUATAN AKHLAK MULIA MELALUI TRADISI MIPIT PARE: Studi Kuantitatif pada Masyarakat Kasepuhan Gelaralam - Jihan Rajmilah; Sekarmaji Sirulhaq (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article stems from concerns about the fading of traditional values amid the tide of modernisation, particularly among indigenous communities in Indonesia. One tradition that remains intact and is believed to embody high moral values is the Mipit Pare tradition among the Kasepuhan Gelaralam community in Sukabumi, West Java. This tradition is not merely a harvest ritual, but also serves as a means of character building through the instilling of values of gratitude, patience, and humility. This study aims to determine the influence of the Mipit Pare tradition on the improvement of noble character among the Kasepuhan Gelaralam community. The research method used a quantitative approach with a causal associative design. Data collection was carried out through questionnaires distributed to 44 respondents from a population of 50 people. The results showed a significant positive influence between the implementation of the Mipit Pare tradition and the improvement of noble character in the community.